Agreement of Ultra-Short-Term Heart Rate Variability Recordings During Overseas Training Camps in Under-20 National Futsal Players - Chen, Yung-Sheng; Pagaduan, Jeffrey C.; Bezerra, Pedro; Crowley-McHattan, Zachary J.; Kuo, Cheng-Deng; Clemente, Filipe Manuel (Frontiers in Psychology, 2021)
Background: Monitoring the daily change in resting heart rate variability (HRV) can provide information regarding training adaptation and recovery status of the autonomic nervous system (ANS) during training camps. However, it remains unclear whether postural stabilization is essential for valid and reliable ultra-short-term (HRVUST) recordings in short-term overseas training camps. Design: Observational and longitudinal study. Purpose: This study aimed to investigate ultra-short-term heart rate variability recordings under stabilization or post-stabilization periods in four overseas training camps. Participant: Twenty-seven U-20 male national team futsal players voluntarily participated in this study. Method: Resting HRV was evaluated for ten minutes during the early morning of each training camp. The natural logarithm of the root mean square of successive normal-to-normal interval differences (LnRMSSD) was used for comparisons. Time segments of HRV were divided into two periods with three measures within each: 1) the first 30-s (1st_30s LnRMSSD), the first 60-s (1st_60s LnRMSSD), and the 5-min standard (1st_5min LnRMSSD) during stabilization; 2) the first 30-s (2nd_30s LnRMSSD), the first 60-s (2nd_60s LnRMSSD), and the 5-min standard (2nd_5min LnRMSSD) after stabilization. Result: The results demonstrated trivial to small ES (-0.03-0.46), very large to nearly perfect ICC (0.76-0.98), and narrow range of SEM (0.06-0.31) when all time segments of HRVUST were compared to the 1st_5min and 2nd_5minHRV. Furthermore, the magnitude of the correlation coefficients ranged from very high to nearly perfect for all the time segments (r = 0.83-0.97). The HRVUST posted excellent agreement in all time segments (bias = -0.05-0.12) with/without postural stabilization. Trivial to small levels of effect size in all time segments of LnRMSSDmean (0.02; 0.41 ES) and LnRMSSDcv (-0.49; -0.02 ES) across overseas training camps was identified. Conclusion: The first 30-s or 60-s LnRMSSD recordings can be used to evaluate daily cardiac-autonomic function during overseas training camps in futsal players. The process for stabilization seems to be unnecessary for measuring the morning resting LnRMSSD in overseas training camps among young adult futsal players.